Rêves de la littérature de divertissement en Chine impériale tardive - Lucas, Aude (Welten Ostasiens / Worlds of East Asia / Mondes de l'Extrême Orient, 2023)
The book offers a cultural, historical and literary study of dream narration in Chinese literature (particularly in the literary genres of xiaoshuo 小說, "petty talk" and biji 筆記, "notebook"). It considers texts from Late Imperial China (13th-19th centuries), with an emphasis on the early/mid-Qing dynasty.